CHARACTERIZATION OF PURPLE CORN PLANTS F2 AND F3 SEEDS (Zea mays L.) FREE PONDS OF MANADO YELLOW CORN WITH PURPLE CORN. - Ratna Juita; Yefta Pamandungan; Edy F. Lengkong (Jurnal Agroekoteknologi Terapan, 2022)
This study aims to determine the characteristics of purple corn F2 and F3 seeds (Zea mays L.) free pollinated Manado Kuning corn with purple corn. The research was carried out in the experimental garden (KP) Pandu, Faculty of Agriculture, Sam Ratulangi University, from July 2019 to October 2019. The research was conducted to describe the growth and yield characters of purple corn obtained from open-pollinated Manado Kuning corn with purple corn using 6 genotypes (cobs) of purple corn, namely: G1 = Genotype 1 purple corn (cob 1), G2 = Genotype 2 purple corn (cob 2), G3 = Genotype 3 purple corn (cob 3), G4 = Genotype 4 purple corn (cob 4), G5 = Genotype 5 purple corn (cob 5), G6 = Genotype 6 purple corn (cob 6). The results of the research on growth components showed that the highest plant height and number of cobs were found in the G5 population (102.71 cm and 1.93) and the highest stem diameter was in the G1 population (2.60 cm). While the yield components in the form of cobs and seeds F3 showed that the highest cob length was found in population G2 (11.57 cm), ear diameter in population G1 (3.17 cm), number of rows of seeds and number of seeds per cob were found in population G5 ( 10.13 and 199.47), the weight of dry cobs with husks and weight of dry cobs without husks were found in the G6 population (51.36 gr and 45.10 gr) and the color of the seeds produced were purple, yellow and white with the percentages respectively 88.11%, 14.82%, 13.28% in population G6, G1 and G3 respectively.Keywords: characterization of corn, purple cornAbstrakPenelitian ini bertujuan mengetahui karakteristik tanaman jagung ungu F2 dan biji F3 (Zea mays L.) hasil bersari bebas jagung Manado Kuning dengan jagung ungu. Penelitian dilaksanakan di kebun percobaan (KP) Pandu Fakultas Pertanian Universitas Sam Ratulangi, pada bulan Juli 2019 sampai dengan Oktober 2019. Penelitian dilaksanakan untuk mendeskripsikan karakter perumbuhan dan hasil jagung ungu yang diperoleh dari persarian bebas (open pollinated) jagung Manado Kuning dengan jagung ungu dengan menggunakan 6 genotipe (tongkol) jagung ungu yaitu: G1 = Genotipe 1 jagung ungu (tongkol 1), G2 = Genotipe 2 jagung ungu (tongkol 2), G3 = Genotipe 3 jagung ungu (tongkol 3), G4 = Genotipe 4 jagung ungu (tongkol 4), G5 = Genotipe 5 jagung ungu (tongkol 5), G6 = Genotipe 6 jagung ungu (tongkol 6). Hasil penelitian pada komponen pertumbuhan menunjukkan bahwa tinggi tanaman dan jumlah tongkol tertinggi terdapat pada populasi G5 (102,71 cm dan 1,93) dan diameter batang tertinggi pada populasi G1 (2,60 cm). Sedangkan pada komponen hasil yang berupa tongkol dan biji F3 menunjukkan bahwa panjang tongkol tertinggi terdapat pada populasi G2 (11,57 cm), diameter tongkol pada populasi G1 (3,17 cm), jumlah baris biji dan jumlah biji pertongkol terdapat pada populasi G5 (10,13 dan 199,47), berat tongkol kering dengan kelobot dan berat tongkol kering tanpa kelobot terdapat pada populasi G6 (51,36 gr dan 45,10 gr) dan warna biji yang di hasilkan yaitu ungu, kuning dan putih dengan persentase berturut-turut 88,11%, 14,82%, 13,28% pada populasi G6, G1 dan G3.Kata kunci: karakterisasi jagung, jagung ungu